Integrating South Sumatera’s local wisdom context into statistical literacy education: An exploration study - Utari, Rahma Siska; Putri, Ratu Ilma Indra; Zulkardi, Zulkardi; Hapizah, Hapizah (Journal of Honai Math, 2024)
Statistical literacy is an essential skill for prospective teachers, as it equips them to become effective educators in an increasingly complex and multicultural society. However, many prospective teachers currently exhibit insufficient proficiency in this area. To address this issue, it is imperative to develop educational programs that prioritize statistical literacy to prepare students to be informed global citizens. This study explores the integration of South Sumatra's local wisdom into statistical literacy education, providing a culturally relevant context for enhancing these skills. The research employs a descriptive qualitative approach consisting of four key stages: problem identification, inductive theorizing, hypothesis testing through observational data, and the processes of replication and refinement. Data collection methods included interviews and observations, which were analyzed qualitatively using triangulation techniques. The findings suggest that incorporating South Sumatra's local wisdom into statistical literacy education is feasible, provided the context meets specific criteria, such as it is rooted in the local wisdom of South Sumatra, it is meaningful and relevant to students, it holds significance for the student's learning experience, it actively engages students in classroom activities, it fosters students' abilities to articulate opinions on civic statistics and their social implications, and it involves statistical scenarios that can be effectively integrated into educational activities. This exploratory study contributes to the theoretical development of statistical literacy education by integrating local wisdom, specifically from South Sumatra, and by introducing these cultural elements to both national and international audiences.